2014
DOI: 10.1111/jph.12315
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Analysis of Powdery Mildew‐Responsive miRNAs in Wheat

Abstract: Wheat powdery mildew, caused by Blumeria graminis f. sp. tritici (Bgt), is one of the most consistently damaging diseases of common wheat worldwide and greatly affects crop productivity. Recently, several plant microRNAs (miRNAs) have been reported as gene expression regulators related to various adverse environments. However, up to now, less is known on the roles of miRNAs in powdery mildew infection response of wheat. In this study, miRNA expression patterns were investigated for identifying Bgt-responsive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
0
7
1
Order By: Relevance
“…miR396 expression was significantly reduced in wheat line JD8 (susceptible) and JD8- Pm30 (resistant line) when infected by Erysiphe graminis f. sp. tritici (Xin et al, 2010), and in wheat accession Shan 4445 (susceptible) when infected by Blumeria graminis (Wu et al, 2015). Overexpression of Sp-miR396a-5p in tobacco leads to enhanced susceptibility to Phytophthora nicotianae infection (Chen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…miR396 expression was significantly reduced in wheat line JD8 (susceptible) and JD8- Pm30 (resistant line) when infected by Erysiphe graminis f. sp. tritici (Xin et al, 2010), and in wheat accession Shan 4445 (susceptible) when infected by Blumeria graminis (Wu et al, 2015). Overexpression of Sp-miR396a-5p in tobacco leads to enhanced susceptibility to Phytophthora nicotianae infection (Chen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The role of miRNAs in the PM response has been reported in wheat (Xin et al, 2010;Wu et al, 2015) and barely (Hunt et al, 2019), but the relationship between miRNAs and cucumber PM resistance is still not clear. The scanning electron microscopy results showed a higher density of PM hyphae on the leaf surface of D8 than on SSSL508-28 48 h after inoculation (Figure 1), which reflected their different responses to PM.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide analysis of miRNAs showed that eight wheat miRNAs from six families (miR394, miR528, miR396, miR171, miR156, and miR160) were differentially expressed upon PM (Blumeria graminis f. sp. tritici Bgt) infection (Wu et al, 2015). More recently, miRNAs related to the response of barley to PM (B. graminis f. sp.…”
Section: Introductionmentioning
confidence: 99%
“…The interactions among the miRNAs and their targets can offer a complex mechanism for the response to stress 23 , 53 . In this study, miRNAs were also sequenced to explore the role of the miRNAs in the regulation of cucumber mRNAs under C. cassiicola infection stress.…”
Section: Discussionmentioning
confidence: 99%
“…In Chinese wild grape, researchers have identified miRNAs that may be involved in powdery mildew resistance 22 . Similarly, under powdery mildew stress, 79 miRNAs were found in wheat leaves 23 . In cucumbers, some researchers have identified a few miRNAs associated with the development and response to stress 24 28 .…”
Section: Introductionmentioning
confidence: 98%